Contributory factors to crane-related accidents in the Thai construction industry - Kongsong, Waranon; Chimpradit, Sayun; Snongtaweeporn, Teeradej; Sumet; Pooworakulchai, Chaiwat; Thammapornram, Chaleeporn (Edelweiss Applied Science and Technology, 2025)
This article aims to study the key factors influencing crane-related accidents in construction operations with the objective of improving safety performance in engineering practice. A quantitative research approach was adopted using a structured rating-scale questionnaire administered to 33 experts possessing extensive experience in crane operation. Descriptive statistical analysis, including the calculation of mean and standard deviation, was performed to identify and rank the contributing factors. The findings revealed an overall mean score of 4.09 (SD = 0.94), indicating a high level of influence. The most critical factor was defective machinery (x̄ = 4.21), followed by substandard or deformed materials (x̄ = 4.18) and non-compliance with operational manuals (x̄ = 4.09). Other notable contributors included inattentive workers (x̄ = 4.06) and unsafe working environments (x̄ = 3.93). These results suggest that mechanical defects exert the greatest impact on crane-related accidents, while human, material, procedural, and environmental aspects also play essential roles. Accordingly, the study recommends implementing proactive maintenance strategies, integrating advanced maintenance technologies, and strengthening workforce competency through continuous professional training to enhance operational reliability and reduce the likelihood of crane-related accidents in construction projects.